DESAIN DAN PERANCANGAN SISTEM KENDALI PENGGULUNG LILITAN KAWAT TEMBAGA PADA ROTOR GENERATOR - Ihsan, Ihsan; Lesmideyarti, Dwi; Aditya, Angga Wahyu (Pogram Studi Sistem Komputer Universitas Serang Raya, 2025)
Collaborative research activities with partners are carried out with the background of wanting to implement appropriate science to provide solutions to problems that occur. Currently, it is very important to implement a technology-based system to help human work be more efficient both in terms of time and cost. The design of this tool seeks to improve the quality and efficiency of copper wire winding by incorporating a Haiwell HMI for monitoring and control in the user interface and utilizing an Outseal PLC for automatic calculation of the turns of generator rotor wire to be wound. The method used to solve this problem uses Waterfall. The error rate and accuracy are calculated using formulas. In this research activity, the implementing team designed a PLC and HMI-based control and monitoring system. The problem faced by partners is that when winding generator rotors they still use the manual method, namely by counting the number of rolls, this method often experiences errors and takes a very long time to complete 1 rotor. The results of this research are compared with the manual method for 2,440 windings in 7 days whereas using this system only takes 3 days with an efficiency level of 57.14%.